2018
DOI: 10.1021/acs.organomet.8b00339
|View full text |Cite
|
Sign up to set email alerts
|

Behind the Scenes of Group 4 Metallocene Catalysis: Examination of the Metal–Carbon Bond

Abstract: This contribution provides the first detailed analysis of the nature of the M–C σ-bond of three alkylated, isostructural group 4 (M = Ti, Zr, Hf) metallocenes, thereby elucidating individual peculiarities of each metal center in the catalytic conversion of olefins. Therefore, the subtle electronic differences of the individual M–C σ-bonds, which are considered crucial for several subprocesses in the coordinative polymerization of olefins, were examined by detailed experimental charge density studies. These stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 113 publications
1
27
0
2
Order By: Relevance
“…The need to break the stronger hafnium–carbon bonds would lead to higher insertion barriers, and hence lowered activity relative to zirconium . More recently, Rieger has suggested that differences in ionic/covalent character of M–C bonds as well as in enthalpy and entropy of activation lead to differences in activity, stereoselectivity and molecular weight control of the group IV metals for the same metallocene ligand …”
Section: Resultsmentioning
confidence: 99%
“…The need to break the stronger hafnium–carbon bonds would lead to higher insertion barriers, and hence lowered activity relative to zirconium . More recently, Rieger has suggested that differences in ionic/covalent character of M–C bonds as well as in enthalpy and entropy of activation lead to differences in activity, stereoselectivity and molecular weight control of the group IV metals for the same metallocene ligand …”
Section: Resultsmentioning
confidence: 99%
“…We also reported various types of Hf-complexes ([N,P]Hf(CH 2 Ph) 3 , [N,P,N]HfMe 2 , and [N,N]Hf(CH 2 Ph) 3 -type) with tetrahydroquinoline and tetrahydrophenanthroline framework, which were also inferior to I in terms of both activity and α-olefin incorporation capability [45,46,47]. The Hf-C bonding character was significantly ionic when compared to those of Zr-C and Ti-C bonding, and steric congestion around Hf-center might be crucial for the high activity [48]. When steric congestion is not significant, the ionic Hf-C bond becomes strong and the insertion of olefin through the Hf-C bond may be less favorable, leading to lowered activity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, preferential aromatic C-H activation, and therefore tolyl rather than benzyl chain ends, would be expected for σ-bond metathesis reactivity [63]. A radical pathway is more consistent with selective toluene activation at the benzylic position [64], and Ti-C bond homolysis is known to be competitive with olefin polymerization, especially at high temperature [65][66][67][68]. The quantitative computational modeling of this reaction required a dedicated benchmark study, which allowed to overcome the difficulties related to a) the 'transferability problem' [69] in the estimates of metal-carbon bond dissociation energies (BDEs) and b) the 1 → 2 particle nature of this reaction that poses a challenge for static DFT methodologies [36].…”
Section: Mechanistic Studiesmentioning
confidence: 98%